A Systematic Review on Infliximab Biosimilar SB2: From Pre-Clinical Data to Real-World Evidence - Macaluso, Fabio Salvatore; Cummings, JR Fraser; Atreya, Raja; Choi, Jaeyun; Orlando, Ambrogio (Expert Opinion on Biological Therapy, 2021)
Introduction: The infliximab biosimilar SB2 was approved in the EU (2016, Flixabi®) and the US (2017, Renflexis®) for the same indications as the reference product (Remicade®) based on a robust analytical and clinical data package. Areas covered: This systematic literature review summarizes available analytical and clinical data on SB2, including randomized controlled clinical trials and real-world evidence studies. Overall, 184 articles and congress abstracts were identified (excluding duplicates), whereof 5 reports on analytical data, four reports on two randomized controlled trials and 13 reports of real-world evidence studies were included. Expert opinion: The available analytical and clinical data support the equivalence of SB2 to the reference product across approved indications. This is further supported by emerging real-world evidence, particularly in extrapolated indications such as inflammatory bowel disease for both infliximab-naïve patients and patients already established on infliximab switching to SB2. Switching from originator or biosimilar infliximab to SB2 including both single and multiple switches was not associated with an increased risk of loss of treatment response or any safety or immunogenicity concerns. Overall, the approved infliximab biosimilar SB2 is safe and effective in clinical practice across licensed indications.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Ankylosing spondylitis; inflammatory bowel disease; infliximab biosimilar; psoriasis; psoriatic arthritis; real-world evidence; rheumatoid arthritis; SB2; switching